Electrical capacitive control of the properties of substances, transported by pipelines - Tarasenko, Irina; Kolomiets, Dmitro; Rudik, K.; Tarasenko, Sergiy (My University, 2012)
In the article considered the new class of three-terminal electrical capacitive means for control the composition of liquid and loose substances, including such transported by pipelines. Such converters are markedly different with accuracy and noise immunity of remote automated control of substances parameters. Considered and analyzed use possibilities of created design of measuring systems for automatic nondestructive integral and differential control the composition of flow substances – raw materials and semi-finished products of food production.
Keywords: dynamic control; динамічний контроль; flow-through sensor; noise immunity; three-terminal; проточний датчик; завадостійкості; проточный датчик; помехоустойчивости; кафедра електропостачання і енергоменеджменту